Intervention, individual, and contextual determinants to high adherence to structured family-centered rounds: a national multi-site mixed methods study - Andrew J. Knighton; Ellen J. Bass; Elease J. McLaurin; Michele Anderson; Jennifer D. Baird; Sharon Cray; Lauren Destino; Alisa Khan; Isabella Liss; Peggy Markle; Jennifer K. O’Toole; Aarti Patel; et al. (Implementation Science Communications, 2022)
Abstract Background Effective communication in transitions between healthcare team members is associated with improved patient safety and experience through a clinically meaningful reduction in serious safety events. Family-centered rounds (FCR) can serve a critical role in interprofessional and patient-family communication. Despite widespread support, FCRs are not utilized consistently in many institutions. Structured FCR approaches may prove beneficial in increasing FCR use but should address organizational challenges. The purpose of this study was to identify intervention, individual, and contextual determinants of high adherence to common elements of structured FCR in pediatric inpatient units during the implementation phase of a large multi-site study implementing a structured FCR approach. Methods We performed an explanatory sequential mixed methods study from September 2019 to October 2020 to evaluate the variation in structured FCR adherence across 21 pediatric inpatient units. We analyzed 24 key informant interviews of supervising physician faculty, physician learners, nurses, site administrators, and project leaders at 3 sites using a qualitative content analysis paradigm to investigate site variation in FCR use. We classified implementation determinants based on the Consolidated Framework for Implementation Research. Results Provisional measurements of adherence demonstrated considerable variation in structured FCR use across sites at a median time of 5 months into the implementation. Consistent findings across all three sites included generally positive clinician beliefs regarding the use of FCR and structured rounding approaches, benefits to learner self-efficacy, and potential efficiency gains derived through greater rounds standardization, as well as persistent challenges with nurse engagement and interaction on rounds and coordination and use of resources for families with limited English proficiency. Conclusions Studies during implementation to identify determinants to high adherence can provide generalizable knowledge regarding implementation determinants that may be difficult to predict prior to implementation, guide adaptation during the implementation, and inform sustainment strategies.